THE INFLUENCE OF DESIGN THINKING AND CREATIVITY ON TEACHER EFFICACY IN 21ST-CENTURY EDUCATION - Dia Anjani; Sutiyono Sutiyono; Komang Komang; Juni Suryanadi (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
ABSTRACT The importance of strengthening teachers’ professional competence in the 21st-century education era is closely linked to teacher efficacy, which plays a crucial role in the success of the learning process. This study emphasizes the need to analyze the influence of design thinking and teacher creativity on teacher efficacy in the context of 21st-century education. A quantitative survey approach was employed, involving a saturated population of 75 Buddhist education teachers in Lampung Province. Data were collected in Bandar Lampung using a Likert-scale questionnaire specifically adapted to measure design thinking, creativity, and teacher efficacy. Prior to the application of multiple linear regression analysis, instrument validity and reliability tests were conducted. The findings indicate that design thinking has a positive and significant effect on teacher efficacy, while teacher creativity also exerts a positive and substantial influence. Simultaneously, both predictor variables enhance the model’s ability to explain the variance in teacher efficacy. This study concludes that teacher efficacy can be strengthened through professional development programs based on studio-style design thinking that integrate empathy, problem interpretation, ideation, prototyping, and testing, as well as through the reinforcement of creative practices within the school environment. ABSTRAK Pentingnya penguatan kompetensi profesional guru di era pendidikan abad ke-21, khususnya terkait efikasi guru yang berperan dalam keberhasilan proses pembelajaran. Pentingnya menganalisis tentang pengaruh pemikiran desain dan kreativitas guru terhadap efikasi guru di era pendidikan abad ke-21. Pendekatan survei kuantitatif digunakan dengan melibatkan populasi jenuh sebanyak 75 guru agama Buddha di Provinsi Lampung. Pengumpulan data dilakukan di Bandar Lampung melalui kuesioner skala Likert yang disesuaikan untuk mengukur pemikiran desain, kreativitas, dan efikasi guru. Sebelum analisis regresi linier berganda diterapkan, dilakukan uji validitas dan reliabilitas instrumen. Temuan penelitian menunjukkan bahwa pemikiran desain memberikan pengaruh positif dan signifikan terhadap efikasi guru, sementara kreativitas guru juga berpengaruh positif dan cukup besar. Secara simultan, kedua variabel prediktor meningkatkan kemampuan model dalam menjelaskan variasi efikasi guru. Penelitian ini menyimpulkan bahwa efikasi guru dapat diperkuat melalui program pengembangan profesional berbasis studio design thought yang mengintegrasikan empati, penafsiran masalah, ideasi, pembuatan prototipe, dan pengujian, serta penguatan praktik kreatif di lingkungan sekolah.